2017
DOI: 10.1063/1.4971980
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of electron temperature in inductively coupled plasma

Abstract: It is generally recognized that the electron temperature Te either remains constant or decreases slightly with plasma power (plasma density). This trend can be simply verified using a single-step or multi-step fluid global model. In this work, however, we experimentally observed that Te evolved with plasma power in radio frequency (RF) inductively coupled plasmas. In this experiment, the measured electron energy distributions were nearly Maxwellian distribution. In the low RF power regime, Te decreased with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Langmuir probes) with relevant theoretical models are available at low pressure. As considerable plasma parameters have been experimentally obtained via such simple diagnostics, they have allowed for further insights into plasma physics, including electron kinetics [27][28][29] and electron heating mechanisms [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Langmuir probes) with relevant theoretical models are available at low pressure. As considerable plasma parameters have been experimentally obtained via such simple diagnostics, they have allowed for further insights into plasma physics, including electron kinetics [27][28][29] and electron heating mechanisms [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The (positive and negative) ions in this drift field are generally considered to be at rest (being non-responsive to the RF electric field alternating at, e.g., 13.56 MHz, due to their heavy masses), while the mobile electrons can instantaneously follow the rapidly alternating electric field and, thus, be accelerated to high energies and cause ionization/excitation. Consequently, in previous studies of such plasmas most of the attention has been paid to the investigation of the electron dynamics [41][42][43][44][45]. The visual appearance of such discharges typically shows a homogeneous bright zone in the central bulk region surrounded by two dark sheath regions adjacent to the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…This is, perhaps, due to the enhancement in the plasma density, i.e., the temperature of electrons or ions. 23 El-Hossary et al 24 studied the impact of plasma power on ZnO thin-film deposition. They observed that an increasing RF plasma power resulted in higher plasma species energy, owing to the increase of the substrate temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It can be stated that on increasing the RF plasma power, the temperature also increases inside the reactor. This is, perhaps, due to the enhancement in the plasma density, i.e., the temperature of electrons or ions . El-Hossary et al studied the impact of plasma power on ZnO thin-film deposition.…”
Section: Resultsmentioning
confidence: 99%